2011
DOI: 10.1021/jp1085334
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Optical Properties of Triphenylene-Based Dendritic Donor Perylene Diimide Acceptor Systems

Abstract: A donor-acceptor charge transfer system based on two discotic mesogens has been synthesized. The donor is either a triphenylene (POG0) or a triphenylene-based conjugated dendron (POG1), while the acceptor is a perylene diimide (PDI) core. The donors are covalently linked to the bay positions of the PDI core through an ether linkage. In chloroform, due to the short donor-acceptor distance and the matching frontier orbital levels, photoinduced charge transfer from either the donor excitation or the acceptor exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 111 publications
1
24
0
Order By: Relevance
“…We have previously reported that a novel type of flying-seed-like liquid crystals show mesomorphism despite absence of long chains [36][37][38][39][40][41]. For example, (m-CH 3 OPhO) 8 PcCu (8) in Fig. 8[A] shows mesomorphism.…”
Section: Homeotropic Alignment Depending On the Presence Of The Methomentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that a novel type of flying-seed-like liquid crystals show mesomorphism despite absence of long chains [36][37][38][39][40][41]. For example, (m-CH 3 OPhO) 8 PcCu (8) in Fig. 8[A] shows mesomorphism.…”
Section: Homeotropic Alignment Depending On the Presence Of The Methomentioning
confidence: 99%
“…1[C]). Furthermore, the (C n S) 6 PcCu-C m -C 60 dyads (2a-c) exhibit homeotropic alignment at rt for (n, m) = (14,8), (14,10), (14,12). Hence, the donor part of hexakistetradecyllthio-substituted PcCu, (C 14 S) 6 PcCu-, may be favourable to induce a room temperature liquid crystalline phase.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies are needed using a new homologue substituted by chiral alky chains. Nevertheless, to our best knowledge, this is the first established example of the helical structure of fullerenes in columnar liquid crystalline donor-acceptor dyads [13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: -6 Helical Structure Of Fullerenes Around Pc Core Columnsmentioning
confidence: 99%
“…They can greatly reduce their costs to manufacture the solar cells. Liquid crystalline D-A systems are braodly classified into three groups: smectic liquid crystals [1][2][3][4], liquid crystalline copolymers [5][6][7][8][9][10][11][12] and discotic columnar liquid crystals [13][14][15][16][17][18][19][20][21][22][23][24][25]. In 2004 Kim et al reported that an organic photovoltaic cell was fabricated by using liquid crystalline N,N'-diheptyl-3,4,9,10-perylenetetracarboxylicdiimide (PTCDI-C7) as the electron acceptor and zinc phthalocyanine (ZnPc) as the electron donor [1].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, it is unfavourable to form both defects and polydomains in the homeotropic alignment [29]. Up to date, there have been some donor-acceptor dyads showing columnar liquid crystalline mesophases [13][14][15][16][17][18][19][20][21][22][23][24][25]. For example, Bushby et al reported in 2005 that a triphenylene derivative connected with fullerene showed columnar mesomorphism [13].…”
Section: Introductionmentioning
confidence: 99%